Redskap och intensitet vid vårbruk till potatis - Edling, Peter (1976)
Different implements for spring tillage and different cultivation intensities of autumn-ploughed fields were studied in eleven field experiments in potatoes in northern Sweden in 1965-69. The implements used were a spring tine harrow, a cultivator-harrow with fairly rigid spring tines and a disc harrow. These implements were used in two, four and six runs. In addition, there was one treatment with spring ploughing and spring tine harrowing (two runs) and one treatment with rotary cultivation (one run). The experiments were carried out on light soils, rich in fine sand and silt. In one of the experiments, however, the soil had a clay content as high as 23 per cent. Among the harrows, the disc harrow gave the best mean yield result. Four runs gave the highest yield. The differenees were, however small. Ploughing in the spring did not increase the crop yield. The rotary cultivation gave a yield result as high as the best of the harrowed treatments.